Performance evaluation of reclaimed asphalt pavement proportion in recycled mix / Mohd Azli Ayob - Ayob, Mohd Azli (2015)
Malaysia spends a substantial amount of money in maintaining the road pavements. Adverse climatic conditions and high traffic volume loads are the major contributing factors for pavement distress and are hazardous to the road users. Asphalt overlay is the conventional technique used in pavement maintenance and rehabilitation. However, alternative technique is being developed to replace the increasingly high cost of asphalt overlays. Pavement recycling has the advantages in terms of reduced cost of the pavement maintenance and preservation of environment by reusing in-situ materials and avoiding disposal of waste. One of the recycling techniques that can be used is the Hot In-Place Recycling (HIPR) technique. The HIPR technique consists either mixing the existing pavement material with rejuvenating agent and/or the addition of virgin HMA to the material. This technique requires the addition of rejuvenating agent in the mixture to rejuvenate the existing aged binder in the RAP. This study was carried out to investigate the volumetric properties and performance of compacted recycled mixes using rejuvenating agent. The recycled mixes were designed using Type 1 (Specialty Mix 4 - Hot In-Place Recycling) gradation and the control mix used was the AC 14 dense graded Hot Mix Asphalt (HMA) designed in accordance with Section 4 of Public Works Department Malaysia’s Standard Specification for Road Works. Marshall Mix Design Method was used to produce control mix samples (0% RAP) and all recycled mixes samples, which consists of 70% RAP, 80% RAP, 90% RAP and 100% RAP. In order to determine the optimum amount of rejuvenating agent to be added into the recycled mix, five different concentrations of rejuvenating agent were added ranging from 0.5 % to 1.7 % by weight of the mix at intervals of 0.3 %. The volumetric analysis was performed to ensure compliance with Marshall requirements. The resilient modulus test was performed to measure the stiffness of the mixes while the Modified Lottman test was conducted to evaluate the moisture susceptibility of these mixes. In addition, the Hamburg wheel tracking test was used to evaluate rutting performance of these mixes. The results obtained showed that there were no substantial differences in volumetric properties, stability values and stiffness properties between the control mix and recycled mixes. It can be concluded that recycled mixes performed as good as the performance of conventional Hot Mix Asphalt (HMA) in term of resilient modulus, moisture susceptibility and rutting. It is recommended that further research be carried out on actual pavement sections using the HIPR technique to ensure the technique is effective to be used for pavement maintenance and rehabilitation.